Predictive Power of Work Situation Awareness by Work Overload and Job Stress among Workers: Implication for Occupational Health - fariba kiani; Ahmad Borjali; Kyomars Farahbakhsh; Noorali Farrokhi (Shiraz University of Medical Sciences, 2015)
Backgrounds: Situation awareness is an important factor in industrial accidents. Improving situation awareness may help to prevent occupational accidents. Determination of factors influencing situation awareness will help to plan and take measures for betterment of working condition and development of a safer workplace. In this study, we examined the role of work overload and job stress in predicting work situation awareness among workers. Methods: This is a cross-sectional study. A sample consisting of 180 employees in National Petrochemical Company in 2014 was selected using stratified random sampling method; the participants filled out the questionnaires containing questions on demography characteristics, work situation awareness of Sneddon, Mearns & Flin (2013), work overload of Beehr, Walsh & Taber (1976), and job stress scale of Cohen and colleagues (1983).The data were analyzed by SPSS software using coefficient correlation and stepwise regression. Statistical differences were considered significant at P<0.001. Results: The results showed that there were internal correlation among work overload, job stress and work situation awareness. Also, the results of stepwise regression analysis revealed that work overload and job stress significantly predicted, respectively, almost 11% and 35% of variances of work situation awareness among workers. Conclusion: Work overload and job stress are two main factors for predicting work situation awareness. To improve workplace safety, interventional measures should focus on enhancing the situation awareness via workload and job stress reduction.